A design strategy of wide angle, broadband tunable near-infrared absorber. (September 2022) - Chai, Xin; Song, Rumeng; Zhang, Yuzhi; Cao, Yunzhen; Liu, Yangqiao; Wu, Lingnan; Ma, Jiayu; Song, Lixin
Abstract: Near infrared absorbers have many applications in the optoelectronic filed. In this study, we design and fabricate two near-infrared broadband tunable absorbers composed of V1-x Wx O2 /HfO2 /Ag layers (the single-layer VO2 absorber) and V1-x Wx O2 /VO2 /HfO2 /Ag layer (the double-layer VO2 absorber). The absorption bands with above 90% of the single-layer VO2 absorber and the double-layer VO2 absorber can be tuned from 1366–1766 nm to 834–980 nm and 931–2000 nm to 845–1056 nm by thermally induced VO2 phase transition, respectively. And the two absorbers we fabricated maintained high absorption over a wide range of incident angles. Furthermore, this paper verified that the introduction of a double-layer absorption layer into the absorber structure can effectively broaden the absorption bandwidth of the absorber and increase the absorption strength. Highlights: Two near-infrared broadband tunable absorbers with perfect absorption are successfully designed and fabricated. The two ultra-thin absorbers maintain high absorption over a wide range of incident angles. The interface of V1-x Wx O2 /VO2 film enhance the absorption performance of the double-layer VO2 absorber.